Effect of powdered vancomycin on stopping surgical site wound infections in neurosurgery: A meta‐analysis - Tian, Bo; He, Yanli; Han, Zian; Liu, Tianjing; Zhang, Xingye (International wound journal, 2023)
We performed a meta‐analysis to evaluate the effect of powdered vancomycin on stopping surgical site wound infections in neurosurgery. A systematic literature search up to July 2022 was performed and 24 137 subjects with neurosurgery at the baseline of the studies; 10 496 of them were using the powdered vancomycin, and 13 641 were not using the powdered vancomycin as a control. Odds ratio (OR) with 95% confidence intervals (CIs) were calculated to assess the effect of powdered vancomycin on stopping surgical site wound infections in neurosurgery using dichotomous methods with a random or fixed‐effect model. The powdered vancomycin had significantly lower surgical site wound infections after spinal surgery (OR, 0.53; 95% CI, 0.41‐0.70, P < .001), deep surgical site wound infections after spinal surgery (OR, 0.45; 95% CI, 0.35‐0.57, P < .001), superficial surgical site wound infections after spinal surgery (OR, 0.60; 95% CI, 0.43‐0.83, P = .002), and surgical site wound infections after cranial surgery (OR, 0.37; 95% CI, 0.22‐0.61, P < .001) compared to control in subjects with neurosurgery. The powdered vancomycin had significantly lower surgical site wound infections after spinal surgery, deep surgical site wound infections after spinal surgery, superficial surgical site wound infections after spinal surgery, and surgical site wound infections after cranial surgery compared to control in subjects with neurosurgery. The analysis of outcomes should be done with caution even though the low number of studies with low sample size, 3 out of the 42 studies, in the meta‐analysis, and a low number of studies in certain comparisons.